Technology of arrangement of underground floors in existing buildings using compressed tube concrete piles - Shpakova, H.; Hrytsiv, B. (Ways to Improve Construction Efficiency, 2023)
The article considers the possibility of arranging underground surfaces in existing buildings using the technology of pressed pipe concrete piles. Traditional and innovative methods of performing works are analyzed, which allow to increase the technical indicators of frame and frameless buildings, to restore and increase the operational characteristics of buildings and structures. Special attention is paid to the technology of pressed-in tubular concrete piles and their application in the arrangement of underground floors by building the floor down as an alternative option for measures to increase the load-bearing capacity of the existing object and a promising direction in the reconstruction and modernization of the functional capabilities of buildings. The article is designed to introduce a relatively new method of restoring and strengthening existing foundations and the use of this method in the arrangement of underground floors and is of significant importance for specialists in the field of construction, architecture and design who are interested in expanding the capabilities of existing buildings and structures and optimizing their use in any -what are the functional purposes of these buildings. The use of pressed-in pipe concrete piles in this context can be an important tool for the modernization and improvement of existing facilities and structures, increasing the useful area without increasing the dimensions of the building in the axes on the one hand, and restoring and increasing the bearing capacity of the existing building foundations on the other. This method can help solve a whole niche of new issues, even of strategic importance, including the arrangement of bomb shelters under existing public buildings, such as kindergartens, schools, universities and other public places where bomb shelters are critically important parts of the building from the point of view of public protection today.